Comment Marcel Mauss croyait à l’origine romaine de la Civilisation - Florence Dupont (Cahiers Mondes Anciens)
In his famous essay, Une catégorie de l’esprit humain : la notion de personne, celle de “moi”, Marcel Mauss transforms the “person” into a witness of the evolution of Western civilization. With the word "person", whose etymology comes from persona, Mauss firmly places Rome at the hinge of an ethnographic analysis of the notion of "person", coupled with a linear historical analysis limited to the West. It is in Rome that the primitive mask, which uniquely singles out he who inherits and wears it, would have become a legal category. However, this reconstitution is historically unfounded and, in the chapter dedicated to the Roman "persona", Mauss elaborates based solely on an intuition and one he fails to substantiate. How could such a fine scholar manage to lose all intellectual integrity? My hypothesis is that the place assigned to Rome (and Greece, for that matter) in the great story of Western civilization poisons historical and ethnographical studies; it is imperative that Rome (or Greece) be at the origins of this civilization’s values.